Labour market digitalization and social class: evidence of mobility and reproduction from a European survey of online platform workers - Martindale, N; Lehdonvirta, V (Oxford University Press, 2023)
The type of work we do as adults is significantly influenced by our parents’ social class. However, digital technologies are transforming the way labour markets work. Candidates are screened using algorithmic decision-making systems. Skills are validated with online tests and feedback ratings. Communications take place online. Could these transformations undermine the advantages that have accrued to workers with privileged backgrounds or reproduce this privilege through digital divides? We examine this question with survey evidence from the online (remote) platform economy, a labour market segment where these digital transformations have progressed furthest (N = 1,001). The results reveal that online platform workers come predominantly from privileged class backgrounds, but we find less evidence of parental class shaping what types of online work they do. We conclude that digital transformations of labour markets may reproduce disparities in access to work but attenuate some class-based differences in the selection of workers by employers.